(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2022)
The aim of this paper is to emphasise the importance of adequately selected literary texts in the English language teaching with the aim of helping students develop intercultural competence. The contemporary society consists of intercultural encounters, in order for the communication to be successful, multicultural teaching is recommended as a potential link between the members of the native and target culture. In this paper, we will emphasize the importance of multicultural texts that should be used in the classroom from an early age to help students not only develop language skills, but also learn about the world, and create a personal and critical attitude towards it. Choosing an adequate text (e.g. picture books, fairy tales, folk tales, short stories, contemporary prose) is of the utmost importance. Depending on the students’ interests, age and the level of language proficiency, well-chosen text and the adequate approach to the literary anlysis will help students develop empathy towards the Other. The application of contemporary cultural theories can affect student’s ability to recognize ideologically colored texts. In this paper, several activities and tips that can be applied in teaching will be proposed in order to help students develop intercultural competence by using literary texts.